Simple and efficient transmission strategies for Device-to-Device caching networks. (April 2018) - Jeong, Moo-Woong; Ryu, Jong Yeol; Ban, Tae-Won
Abstract: For device-to-device (D2D) caching networks, we propose simple transmission strategies in order to minimize the outage probability and maximize the average. We first propose a blanket transmission scheme where multiple caching server devices (CSDs) simultaneously transmit the same content to a RD without any information exchange and signal processing at the CSDs. We also propose an opportunistic transmission scheme where we select a single CSD that has the largest channel gain from a request device (RD), and the selected CSD then transmits the requested content to RD. We derive the outage probabilities and average throughputs and we extend the results to the case of the D2D caching network in the presence of multiple RDs. We also analyze and compare the performances of the proposed transmission strategies according to the threshold rate and transmit signal-to-noise ratio (SNR).